Omkring kampen om menighedsrådene 1909-1912: Frederik VIII og Zahles regering 1909-1910 - Trock, Carl (Kirkehistoriske Samlinger, 2004)
For more than 25 years the conservative party (Højre) had the majority in the Landsting (the Upper House) thanks to a preferential franchise. Because of this the party had stayed in power while the opposition party Venstre gradually had gained the majority in the Folketing (the Lower House) thanks to a general franchise. However, King Christian IX recognized that the majority in the Folketing, with Venstre as the dominating party, ought to form the government and after the change in 1901 (Systemskiftet) the leader of Venstre J. C. Christensen, who was a teacher at a village school, by his own choice became Secretary of Church Affairs and Education. He recognized that the time had come to let people, men as well as women, influence the affairs concerning their own parish church through elected parochial church councils. Furthermore, these councils ought to be participating in the election of a new parish priest. From time immemorial the minority of a congregation had had the right to choose their own vicar, and J. C. Christensen wanted for this right to be improved. His Bill was passed by the Folketing without any major problems but conservative members of the clergy influenced the Højre-majority of the Landsting making them block the Bill. What J. C. Christensen had in mind was a constitution for the Church built on a reform “from below”, an idea that Højre opposed. According to Højre a bill on parochial church councils should go hand in hand with a bill on the appointment of a committee that should compose a constitution for the Church; both bills were passed but they were provisional, expiring on January 1st 1910. In 1905 J. C. Christensen had become Prime Minister, but had withdrawn from the government in 1908 when it was revealed that the Secretary of Justice had committed fraud. Enevold Sørensen became Secretary of Church Affairs etc. and like J. C. Christensen he did not regard the time ready for issuing a constitution for the Church. On the other hand he found it necessary that the Law on parochial church councils should be prolonged in that limited form it had been given by the Landsting in 1903; a Bill was put forward at the parliamentary session of 1908-09. However, for J. C. Christensen this was not enough. He wanted the law improved. Among other things he did not want the parish priest to chair the council, the council should elect its chairman among the members, and the council’s influence on the election of a parish priest should be a prerogative. The Bill was, once again, blocked by the Landsting. In the parliamentary session of 1909-10 the Bill was reintroduced by the Secretary. But before the bill could be passed, the government was reduced to a minority by parties both to the left and to the right - and it was forced to resign. The Secretary of Church Affairs etc. of the left wing (Radikale) minority government that took office late in 1909 did not want that kind of parochial church councils. Instead, he wished for a more open arrangement in which the congregations could elect their parish priest directly among three candidates chosen by the Ministry. Having delivered a sermon each, the candidate who got the majority of the votes should be elected. In several aspects, the Radikale government wanted to demonstrate that it was prepared to advance further than Venstre but the expectations surpassed the abilities and the government had to step down. In the years of 1908-9 Venstre had been divided into several groups or factions but at the general election in 1910 they united again. The party won the election and, once again, formed the government. Among the many reforms, through which Venstre demonstrated as great a wish for reform as did the Radikale, a law emerged giving people influence at parish level. The highly respected teacher at a college (højskole) Jacob Appel became Secretary of Church Affairs etc. He did not favour the organized parish-democracy by J. C. Christensen, but preferred an arrangement like the one of his predecessor: the election of a parish priest should be decided by all members of a congregation at a meeting. However, during the years of 1910-12, until a solution to the question was found, Appel had to realize, that J. C. Christensen was still the most powerful politician in Venstre and that his political line had to be followed; the law on parochial church councils had to be prolonged. Proposing the bill Appel had added some changes: at the election of a new vicar the parochial church council ought to be enlarged in order to include people elected at a congregational assembly and that very same assembly should decide on several other matters, such as the Divine service. At the 1910-11 session the Landsting blocked Appel’s bill, the content of which was almost identical to that of J. C. Christensen. In the session of 1911-12 Appel reintroduced the bill but had, through minor changes, eased the situation concerning the parochial church councils. In consequence, both the Radical party and the Social Democrats (they for the first time) could vote for the bill. This was a victory. - Furthermore, Appel was able to carry through a bill that made it possible for the members of the Church (Folkekirken) to ask a vicar of their own choice to deliver a sermon in their local parish church. Before the government’s resignation in 1913, Appel carried the first bill on the salaries of the vicars through.